Far away and yet so close: urban–rural linkages in the context of multilocal work arrangements. Issue 1 (31st December 2022) - Bürgin, Reto; Mayer, Heike; Kashev, Alexander; Haug, Sigve
ABSTRACT: Digital technologies allow knowledge workers to work from multiple locations in both urban and rural areas, creating urban–rural linkages. Information and communication technologies (ICTs) play a critical role. We used a novel mixed-methods approach to combine quantitative data from laptop and smartphone tracking with qualitative data from ethnographic walk-along observations and semi-structured interviews to analyse the creation of urban–rural linkages and temporary proximity in multilocal work arrangements. The results show that multilocal knowledge workers create urban–rural linkages on demand, thereby generating temporary proximity between the urban and the rural. Yet, the economic embedding of these workers in the rural is limited.